Photophysical studies of zinc and indium tetraaminophthalocyanines in the presence of CdTe quantum dots - Britton, Jonathan (Rhodes University, Faculty of Science, Department of Chemistry, 2010)
CdTe QDs capped with mercaptopropionic acid (MPA) and thioglycolic acid (TGA) were covalently linked to zinc and indium tetraaminophthalocyanines (TAPcs) using N-ethyl-N(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxy succinimide (NHS) as the coupling agents. The results presented give evidence in favour of formation of an amide bond between the MTAPc and CdTe QDs. Both the linked ZnTAPc"“QD complexes and the mixture of QDs and ZnTAPc (without chemical linking) showed Förster resonance energy transfer (FRET), though the linked showed less FRET, whereas the QD interactions with InTAPc yielded no evidence of FRET. Both MTAPcs quenched the QDs emission, with quenching constants of the order of 103"“104Mâˆ’1, binding constants of the order of 108-1010M-1 and the number of binding sites for the MTAPc upon the QD being 2. High energy transfer efficiencies were obtained (in some cases as high as 93%), due to the low donor to acceptor distances. Lastly, both MTAPc were shown to be poor optical limiters because their imaginary third-order susceptibility (Im[Ï‡(3)]) was of the order of 10-17-10-16 (optimal range is 10-9-10-11), the hyperpolarizability (Î³) of the order of 10-37-10-36 (optimal range is 10-29-10-34) and the k values were above one but below ten.
Keywords: Indium; Zinc; Quantum dots; Phthalocyanines; Photochemotherapy; Nonlinear optics; Nanocrystals